Synthesis and Bridgman growth of Ga2S3 crystals - Kokh, Konstantin A.; Lapin, Ivan N.; Svetlichnyi, Valerii A.; Galiyeva, Perizat; Bakhadur, Askar; Andreev, Yury M. 1946- (Key engineering materials)
In this work, Ga2S3 crystals were obtained by vertical Bridgman method. The presence of cracks in the grown crystals was interpreted as a result of phase transition into monoclinic structure during cooling. This suggests the use of another approach for the growth of high quality samples, e.g. chemical transport method or melt-solution method. Maximal transparency range of 0.48-22.5 µm and at least 10 times higher damage threshold to that for GaSe render anisotropic Ga2S3 crystal among the most prospective crystals for nonlinear applications.